Narrativity and myth in epic fantasy open-world videogames. Textual, environmental and performative myths - Antonio Castro Balbuena (Amaltea. Revista de Mitocrítica, 2024)
This essay studies narrativity and myth in the video game. With this objective, we explore the relevance of the narrative elements in this medium, such as the characters and the space, with the inclusion of a unique characteristic: the interaction. Based on the connection of the video game with space stories, such as epic fantasy, we delve into the relevance of myth in open-world video games to propose a classification of myths in this medium: textual myths, closer to tradition and expressed in verbal form; environmental myths, the result of the hypermedia condition of the video game and the player's archaeological behavior; and performative myths, created by the player with his decisions and movements. Finally, this proposal is developed through a brief analysis of two open-world video games: World of Warcraft and Dark Souls III.